1991
DOI: 10.1002/mrd.1080280211
|View full text |Cite
|
Sign up to set email alerts
|

Does in vitro capacitation alter chromatin stability of ejaculated human spermatozoa? cytochemical studies

Abstract: In vitro capacitation of human spermatozoa is commonly evaluated by the progressive motility percent. However its effects on sperm chromatin have hardly been studied. Our aim was to determine the extent to which in vitro capacitation with two treatments (B2 or human follicular fluid) alters the chromatin of human spermatozoa, by using two analytical methods, acridine orange staining and Feulgen-DNA cytophotometric measures. Ejaculates were obtained from 23 men participating in our in vitro fertilization progra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
8
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 22 publications
5
8
0
Order By: Relevance
“…2006; Liu and Baker 2007). In accordance with findings of previous studies (Royere et al. 1991; McNutt et al.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…2006; Liu and Baker 2007). In accordance with findings of previous studies (Royere et al. 1991; McNutt et al.…”
Section: Discussionsupporting
confidence: 94%
“…In addition, sperm treated with heparin penetrated a higher percentage of oocytes than sperm incubated (4 h) with 20% or 60% FF. In brief, a level of 20% FF is non‐physiological and may be incompatible with fertilization (Royere et al. 1991).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It had been reported that the degree of DNA damage is clearly correlated with the impairment of embryo development and severe DNA damage cause male infertility [40]. Moreover, sperm capacitation could alter the chromatin stability, enhance remodeling asynchrony and result in delayed pronuclei formation and DNA synthesis [41], [42]. Our in vivo results showed that the prematurely capacitated sperm stemmed from knockdown of HongrES1 led to the reduction in fertility and somehow deformed appearance of fetuses and pups.…”
Section: Discussionmentioning
confidence: 52%